Efficacy of deltamethrin against ticks on goats in Makhuduthamaga municipality and detection of Ehrlichia ruminantium in Amblyomma hebraeum - Jongejan, Frans (University of Pretoria, 2022)
Dissertation (MSc (Veterinary Science Tropical Diseases))--University of Pretoria, 2019.